NEW DATA ON THE ALIEN VASCULAR FLORA OF CALABRIA (SOUTHERN ITALY) - Musarella, C. M.; Stinca, A.; Cano-Ortíz, A.; Laface, V. L. A.; Petrilli, R.; Esposito, A.; Spampinato, G. (Annali di Botanica, 2020)
New data concerning the distribution of 21 non-native vascular species for Calabria (southern Italy) are presented. Agave filifera is reported for the first time in Europe (Canary Islands excluded), while Leucaena leucocephala subsp. glabrata and Senna corymbosa are indicated for the first time in continental Italy. Saccharum biflorum is confirmed in Italian Peninsula, while Physalis angulata is a new exotic plant for southern Italy. Moreover sixteen other species are reported for the first time, confirmed or indicated with an updated naturalization status in Calabria.